2016
DOI: 10.1016/j.foodchem.2016.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the nutraceutical quality of broccoli sprouts by elicitation

Abstract: Epidemiological studies show an inverse association between Brassica consumption and chronic diseases. Phytochemicals are thought to be beneficial for human health and therefore responsible for this protective effect. Increasing their levels into Brassica food is considered an expedient nutritional strategy that can be achieved through the manipulation of growth conditions by elicitors. In this work we systematically evaluated the influence of treatment with different elicitors (sucrose, mannitol, NaCl, 1-amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 40 publications
4
32
1
2
Order By: Relevance
“…Elicitors, as stimulants, can also affect other pathways not studied in this work (such as flavonoids or vitamin C), determining the differing behavior of the individual GLSs. 55 In our work, in the inflorescences samples at 15 and 30 min, treatment with SA + MeJA gave the highest concentrations of total GLSs (Fig. 2(B)), whereas for the leaf samples, at 15 min, the highest concentration was found for the MeJA treatment ( Fig.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Elicitors, as stimulants, can also affect other pathways not studied in this work (such as flavonoids or vitamin C), determining the differing behavior of the individual GLSs. 55 In our work, in the inflorescences samples at 15 and 30 min, treatment with SA + MeJA gave the highest concentrations of total GLSs (Fig. 2(B)), whereas for the leaf samples, at 15 min, the highest concentration was found for the MeJA treatment ( Fig.…”
Section: Discussionsupporting
confidence: 46%
“…As we have observed in our experiments, elicitation of the starting material influences the GLSs concentration and content of the subsequent extracts. Elicitors, as stimulants, can also affect other pathways not studied in this work (such as flavonoids or vitamin C), determining the differing behavior of the individual GLSs . In our work, in the inflorescences samples at 15 and 30 min, treatment with SA + MeJA gave the highest concentrations of total GLSs (Fig.…”
Section: Discussionmentioning
confidence: 47%
“…Furthermore, MeJA has been reported to enhance the β-carotene content in broccoli sprouts (Natella et al, 2016) and in mango (Muengkaew et al, 2016). Impositions of SA and MeJA on banana plantlets showed positive modulation of MaPSY1 with respect to other genes, delineating its role in plant development, physiology and antioxidant defense mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, sprouts where chosen as they are naturally enriched in bioactive molecules compared to the corresponding mature vegetable [ 18 ], they can be grown under fully controlled environmental conditions, and can easily be treated with elicitors to deliberately and specifically modify their phytochemical content. We found that treatment with sucrose that had been previously reported to elicit the accumulation of glucosinolate and phenolic compounds and to trigger the synthesis of anthocyanins in broccoli sprouts [ 43 , 44 , 45 ] provides the most significant overall effect on phytochemical composition of broccoli sprouts [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, elicitation, i.e., manipulation of growth conditions to trigger the synthesis and accumulation of bioactive secondary metabolites, can be considered a good strategy for functional enrichment of plant-derived foods [ 12 ]. Recently, by systematic evaluation of many different elicitors, we have identified sucrose as the elicitor that provides the most significant overall effect on phytochemical composition of young broccoli seedlings [ 13 ].…”
Section: Introductionmentioning
confidence: 99%